Resettlement of Kazakhs in China in the 20-30s of The XX Century - YESKENDIROV, MEIR; TOKISHKADYROV, BOTABEK; BAYSSARINA, KYMBAT; IBRAYEMOVA, MAIRA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article describes the historical aspects of the resettlement of Kazakhs from eastern Kazakhstan in China. The social and economic position of Kazakhs in the 20-30s, and the motives and reasons for resettlement are designated; the impact of resettlement on the economy, life and traditional culture of Kazakhs is considered. The movement of delegates from the national bourgeoisie, considered from the beginning as the financial aid of Kazakh society, had a negative effect on the monetary and segmental emergency, but also on the decline of the centuries-old customary economy. RESUMEN En este artículo se describen los aspectos históricos del reasentamiento de kazajos provenientes del este de Kazajstán en China. Se designa la posición social y económica de los kazajos en los años 20-30, los motivos y las razones del reasentamiento, y se considera el impacto de éste en la economía, la vida y la cultura tradicional de los kazajos. El movimiento de delegados de la burguesía nacional, considerado desde un principio como la ayuda financiera de la sociedad kazaja, tuvo un efecto negativo en la emergencia monetaria y segmentaria, pero también en la decadencia de la economía consuetudinaria centenaria.